ABDULLAH AVLONI IS A WRITER WHO SANG ABOUT THE IDEAS OF ENLIGHTENMENT AND NATIONAL REVIVAL - Abdusalomova Muslima Gayratjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article argues that Abdullah Avloni’s views in the field of education are closely linked with the psyche, lifestyle, national values of the Uzbek people, his rich pedagogical heritage has served as a valuable source in the development of the national school, national pedagogy.